Gonadal mosaicism of a novel IQSEC2 variant causing female limited intellectual disability and epilepsy - Ewans, Lisa J (Eur J Hum Genet, 2017)
We report a family with four girls with moderate to severe intellectual disability and epilepsy. Two girls showed regression in adolescence and died of presumed sudden unexpected death in epilepsy at 16 and 22 years. Whole exome sequencing identified a truncating pathogenic variant in IQSEC2 at NM_001111125.2: c.2679_2680insA, p.(D894fs*10), a recently identified cause of epileptic encephalopathy in females (MIM 300522). The IQSEC2 variant was identified in both surviving affected sisters but in neither parent. We describe the phenotypic spectrum associated with IQSEC2 variants, highlighting how IQSEC2 is adding to a growing list of X-linked genes that have a female-specific phenotype typically associated with de novo mutations. This report illustrates the need for careful review of all whole exome data, incorporating all possible modes of inheritance including that suggested by the family history.